Validation of the Impact of Event Scale With Modifications for COVID-19 (IES-COVID19) - Vanaken, Lauranne; Scheveneels, Sara; Belmans, Eline; Hermans, Dirk (Frontiers in Psychiatry, 2020)
Viral outbreaks can be experienced as disruptive and can be associated with trauma-related stress symptoms. In the current study, we adjusted the Dutch version of the Impact of Event Scale (IES) to assess traumatic stress symptoms related to the impact of the COVID-19 outbreak. The psychometric properties of this Impact of Event Scale with modifications for COVID-19 (IES-COVID19) were investigated by administering the IES-COVID19 to 380 university students, who participated during the early stage of the COVID-19 outbreak, upon invitation via e-mail. Using confirmatory factor analysis, the factor structure of the IES-COVID19 was found to be similar to the original IES, indicating two latent factors: intrusion and avoidance, χ2(85) = 147.51, CFI = .92, TLI = .90, RMSEA = .044, SRMR = .049. Cronbach’s alpha showed acceptable internal consistency of the total IES-COVID19, α = .75. Pearson’s correlations of the IES-COVID19 over time were also sufficient, demonstrating adequate test-retest reliability, r = .62. Significant correlations (ranging between .15 and .50) between the IES-COVID19 and symptoms of depression, anxiety, stress, stress-related rumination, as well as negative social interactions, demonstrate adequate convergent validity. Overall, the IES-COVID19 shows to be a valid and reliable measure that can be utilized to investigate trauma-related stress symptoms of intrusion and avoidance related to the short- and long-term impact of the COVID-19 outbreak.